COVID-19 vaccine had a significant positive impact on patients with SARS-COV-2 during the third (Omicron) wave in Saudi Arabia. Issue 11 (November 2022) - AlBahrani, Salma; AlBarrak, Ali; Al-Musawi, Tariq; AlGubaisi, Nawal Ali; Almalki, Maram; Hakami, Fatimah H.; Alghamdi, Turki; AlBeiuruti, Zena; Alkhrashi, Sausan; Almershad, Meshael; Alzahrani, Samira; AlQuraiaan, Amerah; et al.
Abstract: Introduction: The third (Omicron) wave had caused significant increase in the number of COVID-19 cases around the globe. The severity of the disease dependeds on the extent of the vaccination status. Methods: This is a retrospective study of infected COVID-19 patients during the third (Omicron) wave in a hospital in Saudi Arabia. Results: A total of 400 patients were included with 220 (55 %) males and 180 (45 %) females, and a mean age (+/- SD) of 36.34 + 16.47 years. The most common presenting symptoms were: sore throat 159 (39.8 %), cough 158 (39.5 %), fever 132 (33 %), headache 122 (30.5 %), and muscle ache 124 (31%). There was no difference in underlying conditions, signs and symptoms between males and females apart from the occurrence of sore throat with an OR of 2.014 (95 % CI: 1.103–3.677, P = 0.023) and need of hospitalization OR 2.457 (95 % CI: 1.168–5.167, P value =.018) in a binary logistic regression comparison. The need for hospitalization was inversely related to the number of COVID-19 vaccination doses. The rate of admission was 8 (72.7 %), 34 (12 %), 4 (5.4 %) for one, two, and three doses of COVID-19 vaccine, respectively (P < 0.0001). Of all the patients, 14 (3.5 %) and 8 (2 %) required intensive care (ICU) admission and mechanical ventilation, respectively. The median Ct-value of SARS-CoV-2 was higher in those who had 2 or 3 doses compared to those who had one dose of the COVID-19 vaccine, but the difference did not reach statistical significance. None of the included patients died during the study period. Conclusion: Omicron variant symptoms among infected patients are generally milder compared to other variants. Prior COVID-19 vaccination may limit disease severity and need for hospitalization.